Multiplication Operator with BMO Symbols and Berezin Transform - Xue Feng; Kan Zhang; Jianguo Dong; Xianmin Liu; Chi Guan (Journal of Function Spaces)
We discuss multiplication operator with a special symbol on the weighted Bergman space of the unit ball. We give the necessary and sufficient conditions for the compactness of multiplication operator on the weighted Bergman space of the unit ball.